NOX2/NLRP3-Inflammasome-Dependent Microglia Activation Promotes As(III)-Induced Learning and Memory Impairments in Developmental Rats - Linlin Zhang; Yuyao Xiao; Dan Wang; Xuerong Han; Ruoqi Zhou; Huiying Zhang; Kexin Zhu; Junyao Wu; Xiance Sun; Shuangyue Li (Toxics)
Inorganic arsenic [As(III) and As(V)] is a pervasive environmental contaminant in groundwater systems, early-life exposure to which is associated with an impaired cognitive ability and an increased risk of neurobehavioral disorders. Although the effect of As(III) on the neurons is well studied, the involvement of the microglia remains unclear. In this study, the effects of sodium arsenite (NaAsO2) on microglial activation and the underlying NLRP3 inflammasome mechanism were determined. Pregnant rats were gavaged with NaAsO2 (0, 1, 4, and 10 mg/kg body weight), which dissociates in aqueous solutions into bioactive arsenite species [As(OH)3], from gestational day 1 (GD1) to postnatal day 21 (PND21). The results showed that As(III) induces learning and memory impairments and microglial activation in the hippocampus of offspring rats (PND21). Increased expression of NLRP3, the activation of caspase-1, and the production of interleukin-1β were observed in both the hippocampus of As(III)-exposed offspring rats and As(III)-exposed microglial BV2 cells under culture conditions. Interestingly, blocking the NLRP3 inflammasome using MCC950 mitigated its activation. Furthermore, inhibition of NADPH oxidase 2 (NOX2) using apocynin or specific siRNA significantly reduced As(III)-induced microglial NLRP3 inflammasome activation. In addition, inactivation of the microglial NLRP3 inflammasome or NOX2 markedly rescued As(III)-induced neurotoxicity in the hippocampal HT22 cells. Taken together, this study reveals that NOX2/NLRP3-inflammasome-dependent microglial activation promotes As(III)-induced learning and memory impairments in developmental rats.